Adaptive live streaming system performance of MMT and DASH over a deployed LTE network. Issue 13 (1st June 2016) - Cho, Y.; Park, S.; Kim, K.; Suh, D.Y.
Abstract : Moving Picture Expert Group (MPEG) media transport and dynamic adaptive streaming over Hypertext Transfer Protocol are compared, which have been standardised by the MPEG for internet‐based video services. Their performances as adaptive live streaming systems are evaluated over a deployed long term evolution network. The results provide their operational limitations and optimal operation parameters to improve resource usage and the quality of the users' experience.